혈액암 患者에게 실행한 韓方音樂治療 요법이 백혈구內 ANC(절대호중구수)수치 증가에 미치는 영향 - Lee Seung hyun(李承炫); Baik You sang(白裕相); Park Mi ra(朴美羅); An Jiwon(安智媛) (대한한의학원전학회지, 2005)
The purpose of this research is to discover changes of WBC and ANC numbers before and after applying Oriental medicine therapy to blood cancer patients. After that, appropriate music therapy method was well planned and carried for patients. Demonstration and music were conducted according to Ohaeng theory. The oriental music therapy was conducted three hours everyday by listening to music and we made patients participate in playing the instrument for one hour in two times a week. The result was verified in three ways by checking and comparing numbers of WBC, ratio of ANC and New Trophil before and after the experiment. In addition to that verification, we analyzed patients' survey and their response after treatment. The result was that WBC and ANC were efficient as p=0.0419, p=0.0262 each and the ratio of New trophil was not efficient in p=0.999, but partially increased. KCI Citation Count: 5